Initial Breakdown Pulse Parameters in Intracloud and Cloud‐to‐Ground Lightning Flashes. Issue 4 (24th February 2018) - Smith, E. M.; Marshall, T. C.; Karunarathne, S.; Siedlecki, R.; Stolzenburg, M.
Abstract: This study analyzes the largest initial breakdown (IB) pulse in flashes from four storms in Florida; data from three sensor arrays are used. The range‐normalized, zero‐to‐peak amplitude of the largest IB pulse was determined along with its altitude, duration, and timing within each flash. Appropriate data were available for 40 intracloud (IC) and 32 cloud‐to‐ground (CG) flashes. Histograms of amplitude of the largest IB pulse by flash type were similar, with mean (median) values of 1.49 (1.05) V/m for IC flashes and −1.35 (−0.87) V/m for CG flashes. The largest IB pulse in 30 IC flashes showed a weak inverse relation between pulse amplitude and altitude. Amplitude of the largest IB pulse for 25 CG flashes showed no altitude correlation. Duration of the largest IB pulse in ICs averaged twice as long as in CGs (96 μs versus 46 μs), and all of the CG durations were <100 μs. Among the ICs, there is a positive relation between largest IB pulse duration and amplitude; the linear correlation coefficient is 0.385 with outliers excluded. The largest IB pulse in IC flashes typically occurred at a longer time after the first IB pulse (average 4.1 ms) than was the case in CG flashes (average 0.6 ms). In both flash types, the largest IB pulse was the first IB pulse in about 30% of the cases. In one storm all 42 IC flashes with triggered data had IB pulses. Key Points: Range‐normalized amplitude of the largest IB pulse per flash (RNALIB ) averaged 1.49 V/m for 40 ICs and −1.35 V/m for 32 CGs in four storms Average altitude of the largest IB pulse was 9.1 km in ICs and 6.0 km in CGs, with weak inverse relation between altitude and RNALIB for ICs The largest IB pulse is usually within 2 ms (CG) and 8 ms (IC) of the first IB pulse; in one third of cases the largest IB pulse was first